Enhanced Electrocatalytic Oxidation of Methanol on Pt‐Decorated Bi2WO6/Graphene Nanosheets with Visible Light Assistance. Issue 9 (13th July 2020) - Gao, Haifeng; Yuan, Chen; He, Zhilong; Xu, Qiyan; Zhai, Chunyang; Zhu, Mingshan
Abstract : Noble metal/semiconductor–based electrocatalysts have been proverbially used as the anode material in direct methanol fuel cells (DMFCs) recently. Combined with the advantage of the properties of noble metals and semiconductors, photo‐assisted electrocatalytic methanol oxidation is a valid route to increase the catalytic activity of catalysts in DMFCs. Herein, a 2D composite of bismuth tungstate/reduced graphene oxide (Bi2 WO6 /RGO) with excellent optical, electrical, and thermal stability is used as the support for the decoration of platinum nanoparticles (Pt NPs) to synthesize a new electrocatalyst of Pt‐Bi2 WO6 /RGO. Under ambient conditions, the methanol oxidation reaction (MOR) activity of the Pt‐Bi2 WO6 /RGO electrocatalyst increases relative to the Pt/Bi2 WO6 electrode. Note that, under visible light irradiation, it deals with big enhancement of methanol oxidation activity on Pt‐Bi2 WO6 /RGO electrode, highlighting the effect of RGO used as Bi2 WO6 cocatalysis for the MOR activity under illumination. Meanwhile, the corresponding reaction mechanisms with/without visible light are presented, and the roles of Pt‐Bi2 WO6 /RGO for photo‐assisted electrochemical reactions are proposed. Abstract : The introduction of reduced graphene oxide (RGO) nanosheets and assistance of visible light can efficaciously promote the catalytic activity and long‐term stability of methanol oxidation reaction of Pt‐Bi2 WO6 /RGO heterojunction. The favorable photoelectrocatalytic performance of Pt‐Bi2 WO6 /RGO electrode is attributed to the synergistic effect of the photocatalytic and electrocatalytic process.